On Historiography of Fights for Independence and Creation of Lithuanian Army - Lesčius, Vytautas (Lietuvos istorijos studijos, 2002)
Depending on political, social, cultural and other factors, the historiography of the analysed period should be divided into several parts. The first period comprises the time when Bolshevism was gaining strength, i.e., 1917-1919 events, which the Lithuanian soldiers serving in the Russian army experienced. Their diverse activity was elucidated in the periodical press. A lot of published works, reminiscences, and estimation of more important military, political, social events appeared when the army was being created in Lithuania itself (in 1918-1920). Nevertheless, the most part of them remained as a certain "material to history." In the period between the wars (1921-1940), weighty publications came out which reviewed the activity of the army—journals on warfare and history, memoirs, etc. In Soviet times the problem was hardly investigated. The greatest contribution in this field was made by some Lithuanian war historians living abroad. In current Lithuania, the interest of the public in the subject has borne fruit—some extensive works based on the material drawn from archive stocks and other sources have been published, scientific journals come out, etc. This makes it reasonable to believe that the backwardness in the field will disappear in the near future.